An Alternate Synthesis of Bosentan Monohydrate, an Endothelin Receptor Antagonist - Pradeep, Rebelli; Jayaprakash Rao, Yerrabelly; Kumari Bharathi, Yalamanchili; Subbanarsimulu, Porala; Venkat Reddy, Ghojala; Kondal Reddy, Bairy (Synlett, 2014)
An alternate synthesis of an endothelin receptor antagonist bosentan monohydrate is reported. This new synthetic route involves the coupling of p-tert-butyl-N-[6-chloro-5-(2-methoxy-phenoxy)(2,2′-bipyrimidin)-4-yl]benzene sulfonamide with commercially available raw material (2,2-dimethyl-1,3-dioxolan-4-yl)methanol as the key step. Attractive features of this approach are its versatileness, commercial availability of raw materials, usage of eco-friendly reagents, and it efficiently provides the desired bosentan monohydrate free from reported impurities such as dimer, N-alkylated, and pyrimidinone impurities.
Keywords: alternate synthesis; bosentan monohydrate; eco-friendly reagents; dimer impurity; N-alkylated; pyrimidinone